Cognitive and Intermedial Semiotics - Silvera-Roig, Marta; López-Varela Azcárate, Asunción (IntechOpen, 2020)
Cognitive and Intermedial Semiotics offers a window into applied cognitive semiotics with different examples of meaning production studies. Thus, in its chapters we will find examples of different approaches, methods, and theories that cognitive semiotics offers as an interdisciplinary field.